A REVIEW ON TRANSDERMAL PATCHES USED AS AN ANTI-INFLAMMATORY AGENT - CHOUDHURY, DEIJY; DUTTA, KOUSHIK NANDAN; KALITA, RAMEN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
The transdermal drug delivery system is widely accepted due to its numerous advantages as it is a non-invasive drug administration process with prolonged therapeutic effect, reduced side effects, improved bioavailability, better patient compliance, and easy termination of drug therapy. Non-steroidal anti-inflammatory drugs such as Diclofenac sodium, Lornoxicam, Aceclofenac, Ibuprofen, antihypertensive drugs, for example, Repaglinide, Atenolol, and Antiviral agents such as Stavudine, zidovudine represents the most commonly used medications for the treatment of pain and inflammatory reaction but various side effects can limit their use. Therefore, transdermal delivery of these drugs has advantages of avoiding hepatic first-pass effect, gastric irritation and delivering the drug for an extended period of time at a sustained level. The present article mainly focuses on the work been done on these drugs by formulated and delivered as transdermal patches to decrease the side effects related to the oral delivery.